Pulsed processing by cold plasma, applied to industrial emission control - Van Heesch, E. J. M.; Huiskamp, T.; Yan, K.; Beckers, F. J. C. M.; Smulders, H. W. M.; Winands, G. J. J.; Lemmens, R. H. P.; Blom, P. P. M.; Segura, S. Davalos; Hoeben, W. F. L. M.; Van Paasen, S. V. B.; Van Oorschot, J. J.; et al. (Frontiers in Chemistry, 2024)
We describe robust cold plasma systems and their industrial application such as airborne VOC (volatile organic compound) abatement and odor control. For odor control, a comparison will be made with odor control by plasma injection. We show that up to 99% of volatile pollution can be removed at an acceptable energy requirement. To explain the test data a solution of global reaction kinetics was developed. It involves the Lambert function and, for convenience, a simple approximation of it. The latter shows that the amount of removal, in good approximation, is a function of a single variable. This variable is electric plasma power divided by gas flow divided by input concentration. We conclude by looking into future efficiency enhancements by implementation of (sub)nanosecond pulsed plasma and solid state high-voltage technology and by integration with catalyst technology.